Experiential intelligence : harness the power of experience for personal and business breakthroughs - Kaplan, Soren (Ascent Audio, 2023)
Experiential Intelligence reveals how our past life experiences impact our present success and future opportunities in ways we often don't recognize. While you can't change what's happened to you or how you've responded to it, within your unique stories are hidden strengths waiting to be discovered. Do just that by uncovering your Experiential Intelligence (XQ)-the mindsets and abilities gained from your personal and professional life experiences. Just as memorizing facts doesn't give you a high IQ, your Experiential Intelligence isn't merely what you've learned over time. It's how you view opportunities, perceive challenges, and tackle goals. XQ is your unique internal fingerprint. You can leverage it to: become a better leader; hire and develop talent using more strategic criteria; increase collaboration, innovation, and results; and transform your organization's culture. Experiential Intelligence reveals the psychological, sociological, and neurological forces that make us tick. Learn how to uncover your hidden assets, remove invisible barriers limiting peak performance, and amplify strengths to achieve breakthroughs for yourself, your team, and your organization.